2015
DOI: 10.1186/s12866-015-0540-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of virulence gene signatures associated with diarrhoeagenic and non-diarrhoeagenic pathovars of Escherichia coli isolates from some selected rivers in South-Western Nigeria

Abstract: BackgroundDiarrhoeal diseases are attributable to unsafe water stemming from improper sanitation and hygiene and are reportedly responsible for extensive morbidity and mortality particularly among children in developed and developing countries.MethodsWater samples from selected rivers in Osun State, South-Western Nigeria were collected and analyzed using standard procedures. Escherichia coli isolates (n=300) were screened for 10 virulence genes using polymerase chain reaction for pathotyping.ResultsWhile the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 93 publications
(97 reference statements)
8
34
3
Order By: Relevance
“…Similar results were found in subSaharan Africa and others countries [2,26,27,28]. ETEC causes a significant number of cases of childhooddiarrhoea and gastroenteritis among the most common agent of traveller'sdiarrhoea with food and water implicated as the modes of transmission [3]. In our study, we did not found ETEC but co-infections was found with EAEC.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar results were found in subSaharan Africa and others countries [2,26,27,28]. ETEC causes a significant number of cases of childhooddiarrhoea and gastroenteritis among the most common agent of traveller'sdiarrhoea with food and water implicated as the modes of transmission [3]. In our study, we did not found ETEC but co-infections was found with EAEC.…”
Section: Discussionsupporting
confidence: 91%
“…EPEC infection is primarily a disease of infants younger than 2 years of age. Numerous case-control studies in many countries have found that EPEC is more frequently isolated from children with diarrhoea than from healthy controls [2,3].However, in our study, the detection rate of EPEC strains from adults with diarrhoea was low (only one typical EPEC) and it co-infection with EAEC. In this study no EPEC was detected from children under five years.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations